SCOLIOSIS - Saime Ay,; Süreyya Ergin, (Archives of Rheumatology, 2006)
In healty vertebral column the vertebrae lie in coronal and transverse plane. Scoliosis is a lateral deviation of the normal vertical line of the spine. Scoliosis is not a disease, a sign, a deformity and can be the result of many diseases. It can be grouped as structural and nonstructural. It is the most common deformity of the spine. For this reason it is important to have early diagnosis and treatment for the scoliosis. Early diagnosis and preoperative rehabilitation is crucial. (Rheumatism 2006; 21: 27-30)